FEASIBILITY OF LOCAL WISDOM BASED BOOKLET TEACHING MATERIALS IN MALIRAN FOREST ON BIODIVERSITY MATERIAL FOR CLASS X STUDENTS - Apriliatul Qoidah, Eka; Puspita Anggraini, Dian; Sholihah, Mar'atus (Universitas Islam Balitar, 2018)
The study aims to determine the feasibility of local wisdom based booklet teaching materials in Maliran forest on biodiversity material for class X students. The type of research used in study is research and development research. The development model used is the Thiagarajan, dkk. (1974) which is limited to develop stage. The booklet is validated by a team of experts including material experts, media expert, and linguistic.. The results of the validation by the expert team get an average percentage of 75,3% with a decent category. The readability test results by class XI students get a percentage of 78% with a decent category. Based on the result of the validation that has been obtained, it shows that the local wisdom-based booklet teaching material in Maliran forest is worthy of being in biodiversity material for class X students.